2017
DOI: 10.1155/2017/7412865
|View full text |Cite
|
Sign up to set email alerts
|

The Noninvasive Treatment for Sentinel Lymph Node Metastasis by Photodynamic Therapy Using Phospholipid Polymer as a Nanotransporter of Verteporfin

Abstract: Aim. The usefulness of photodynamic therapy (PDT) for treating sentinel lymph node (SLN) metastasis was evaluated. Materials and Methods. Verteporfin, a hydrophobic photosensitizer, forms a soluble aggregate with poly(2-methacryloyloxyethyl phosphorylcholine-co-n-butyl methacrylate) (PMB). The concentrations of verteporfin were determined by measuring the fluorescence emitted at 700 nm. Seven days after the inoculation of A431 cells at the forearm of BALB/c nude mice, PMB-verteporfin was injected at dorsum man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…An excellent example of a clinical application of photochemistry is photodynamic therapy (PDT), which involves the light activation of photosensitizers to generate reactive oxygen species to treat various diseases such as actinic keratosis, non-small cell lung cancer, and head and neck cancer. In addition to treating primary diseases originating in a particular part of the body, PDT can be leveraged to target disseminated diseases with appropriate drug delivery carriers, targeting moieties, and optical technologies. For example, a study by Shimada et al combined a phospholipid polymer with a photosensitizer to treat sentinel lymph node metastasis of breast cancer . In another study, intralipid infusion was used to scatter light for activation of photosensitizers in the peritoneal cavity for the treatment of disseminated cancer. , Many photosensitizers that have been successfully employed in the clinic, including chlorin e6, protoporphyrin IX, and benzoporphyrin derivative (BPD, aka.…”
mentioning
confidence: 99%
“…An excellent example of a clinical application of photochemistry is photodynamic therapy (PDT), which involves the light activation of photosensitizers to generate reactive oxygen species to treat various diseases such as actinic keratosis, non-small cell lung cancer, and head and neck cancer. In addition to treating primary diseases originating in a particular part of the body, PDT can be leveraged to target disseminated diseases with appropriate drug delivery carriers, targeting moieties, and optical technologies. For example, a study by Shimada et al combined a phospholipid polymer with a photosensitizer to treat sentinel lymph node metastasis of breast cancer . In another study, intralipid infusion was used to scatter light for activation of photosensitizers in the peritoneal cavity for the treatment of disseminated cancer. , Many photosensitizers that have been successfully employed in the clinic, including chlorin e6, protoporphyrin IX, and benzoporphyrin derivative (BPD, aka.…”
mentioning
confidence: 99%
“…Specifically, photodynamic therapy (PDT) has attracted attention as a minimally invasive treatment. A study of a rodent model of lymph node metastasis employed PDT 25 . In this study, A431 cells were injected to the forelimbs of BALB/c nude mice to develop lymph node metastasis, 2-methacryloyloxyethyl phosphorylcholine -verteporfin was subsequently injected at the dorsum manus, and 75 J of light was delivered to the skin.…”
Section: Discussionmentioning
confidence: 99%
“…There are several limitations in the present study. We used A431 cells as we did in previous studies 23,25 . To better assess the clinical relevance of our model, we plan to use cell lines or primary tumour cells derived from other cancers (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak size of the PLGA-VP-TAT NPs in PBS with and without 10% FBS showed a slight increase during the first 4 h but then remained constant for the next few 48 h (Figure 1e), indicating that there was no significant aggregation in biological media. The % release of VP from the PLGA-VP NPs in PBS suspension at 37 • C was plotted as a function of time (Figure 1f), and showed that, after some initial release in the first 4 h, >95% of the VP remained trapped within the NPs (Figure 1e), likely due to VP being highly hydrophobic with a low affinity for the hydrophilic environment outside the PLGA matrix [41]. This drug release profile is consistent with our previous findings [17].…”
Section: Plga-vp and Plga-vp-tat Nanoparticle Characterisationmentioning
confidence: 99%